Molecular cloning of a gene encoding a 45,000-dalton polypeptide associated with bile acid 7-dehydroxylation in Eubacterium sp. strain VPI 12708. - White, W B (1988)
Eubacterium sp. strain VPI 12708 is an intestinal anaerobic bacterium which possesses an inducible bile acid 7-dehydroxylation activity. Two cholic acid-induced polypeptides with apparent molecular weights of 27,000 and 45,000, respectively, coeluted with bile acid 7-dehydroxylation activity upon anaerobic high-performance gel filtration chromatography of crude cellular protein extracts. The 45,000-dalton polypeptide was purified to greater than 95% homogeneity by high-performance liquid chromatography gel filtration and high-performance liquid-DEAE chromatography. The first 28 amino acid residues of the N terminus of this polypeptide were determined by gas-phase sequencing, and a corresponding mixed oligonucleotide (20-mer) was synthesized. Southern blot analysis of EcoRI total digests of chromosomal DNA showed a 2.6-kilobase fragment which hybridized to the 32P-labeled 20-mer. This fragment was enriched for by size fractionation of an EcoRI total digest of genomic DNA and ligated into bacteriophage lambda gt11. Recombinant phage containing the putative gene encoding the 45,000-dalton polypeptide were detected with the 32P-labeled 20-mer by plaque hybridization techniques. The insert was 2.6 kilobases in length and may contain the entire coding sequence for the 45,000-dalton polypeptide. The 2.6-kilobase insert was subcloned into pUC8 and transformed into Escherichia coli DH5 alpha. However, the 45,000-dalton polypeptide was not detected in cell extracts of this organism when specific antibody was used. Preliminary nucleic acid sequence data correlated exactly with the amino acid sequence. A cholic acid-induced mRNA species of greater than 6 kilobases in size was identified by Northern (RNA) blot analysis of total RNA, suggesting that the gene coding for this polypeptide is part of a larger operon.